Pemanfaatan Sampah Plastik UMKM Sebagai Media Kolase Kreatif Untuk Meningkatan Kesadaran Lingkungan Pada Anak Usia Dini - Syaputra, Erpan; Novita, Meta; Concesa, Maria; Jefriansyah, Moehammad; Azhari, Nirman; Yanto, Yanto; Susena, Karona Cahya; Abi, Yudi Irawan (Jurnal Kewirausahaan & Inovasi, 2025)
This study aims to analyze the effectiveness of utilizing plastic waste from Micro, Small, and Medium Enterprises (MSMEs) as a creative collage medium to increase environmental awareness among early childhood students. Using a quantitative quasi-experimental method with a pretest-posttest control group design, this research involved 8 children aged 5–12 years from two early childhood education institutions in Bengkulu. The experimental group received environmental education using creative collages made from MSME plastic waste, while the control group used conventional media. Data were collected using an environmental awareness scale and analyzed using paired and independent t-tests. The results showed a significant increase in the environmental awareness scores of the experimental group compared to the control group (p < 0.05). This study concludes that integrating recycled materials from MSME plastic waste into creative learning activities significantly enhances environmental consciousness among young children.